1999
DOI: 10.1002/1529-0131(199901)42:1<61::aid-anr8>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancy between regional cerebral blood flow and glucose metabolism of the brain in systemic lupus erythematosus patients with normal brain magnetic resonance imaging findings

Abstract: Objective. In this study, 2 updated brain-imaging modalities, technetium-99m hexamethylpropylene amine oxime-single-photon-emission computed tomo-graphy (HMPAO-SPECT) and fluorine-18 2-fluoro-2-deoxy-D-glucose-positron emission tomography (FDG-PET), were used to simultaneously detect regional cerebral blood flow (rCBF) and glucose metabolism of the brain in patients with systemic lupus erythematosus (SLE). Methods. Twenty-five female SLE patients, ages 25-40 years, were enrolled in this study and assigned to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
53
0
7

Year Published

2000
2000
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 30 publications
4
53
0
7
Order By: Relevance
“…For example, several studies reported either glucose hypometabolism or hypoperfusion in the temporal, parietal, and frontal lobes (Stoppe et al 1990;Lin et al 1997;Kao et al 1999). Weiner et al (2000) found hypometabolism in similar areas including the frontal lobes, but little involvement of temporal areas.…”
Section: Brain Imaging Findings In Slementioning
confidence: 99%
See 2 more Smart Citations
“…For example, several studies reported either glucose hypometabolism or hypoperfusion in the temporal, parietal, and frontal lobes (Stoppe et al 1990;Lin et al 1997;Kao et al 1999). Weiner et al (2000) found hypometabolism in similar areas including the frontal lobes, but little involvement of temporal areas.…”
Section: Brain Imaging Findings In Slementioning
confidence: 99%
“…Weiner et al (2000) found hypometabolism in similar areas including the frontal lobes, but little involvement of temporal areas. Using high resolution instrumentation with SPECT, Kao et al (1999) detected deficits in deeper brain structures such as the basal ganglia.…”
Section: Brain Imaging Findings In Slementioning
confidence: 99%
See 1 more Smart Citation
“…Die häufige Beteiligung der parietalen und temporalen Region wird mit dem höheren Risiko für Mangelperfusion im Grenzscheidengebiet zwischen A. cerebri media und A. cerebri posterior interpretiert [18]. Multifokale Areale gestörten zerebralen Blutflusses finden sich bei 77-100% der untersuchten Patienten mit schwerer zerebraler Symptomatik, bei 33-85% der Patienten mit milder Symptomatik, aber auch bei asymptomatischen Patienten in 10-29% [27,50,60,89,91]. Eine mögliche Erklärung für Perfusionsdefizite bei asymptomatischen Patienten ist, dass diese umschriebenen Foci nur funktionell stumme Hirnareale betreffen.…”
Section: ❑ Spectunclassified
“…Kodama ÜBERSICHT 0-40% bei asymptomatischen Patienten [50,101,110]. Im Gegensatz dazu wurde in einer Studie ein erniedrigter Glucosemetabolismus nur bei Patienten mit zahlreichen Marklagerläsionen im MRT nachgewiesen [93].…”
Section: ❑ Spectunclassified